The Role France Played in the Political Life of Chad and Other Former African Colonies - Rosta, Gabriella (Honvédségi Szemle – Hungarian Defence Review, 2025)
Chad, a former French colony in the heart of the African continent, has always been a region that, until recently, seemed very remote and of little interest to the Hungarian people. However, the Hungarian government’s plan for the Hungarian Defence Forces to set up a possible military mission in Chad with the participation of 200 Hungarian service members has drawn attention to the situation and events in the region. The Sahel region is today considered the most dangerous and unstable region in the world, characterised by the presence and operation of numerous terrorist organisations and frequent coups d’état, forcing millions of people every day to start a new life as refugees on the European continent, leaving their homes or perhaps their countries of origin. In this article, we review the various historical, geographical, economic, and political factors that have led to this situation, the current situation and its likely outcome, and the role and responsibility of France.